Prevalence of temporomandibular dsorders and association with psychological factors in students of undergraduate Dentistry students - George Azevedo Lemos; Pâmela Lopes Pedro da Silva; Marcília Ribeiro Paulino; Vanderlúcia Gomes Moreira; Rejane Targino Soares Beltrão; André Ulisses Dantas Batista (Editorial Ciencias Médicas, 2015)
Introduction: the approach of biopsychosocial factors have gained prominence when considering the multifactorial nature of Temporomandibular Disorders but some studies present conflicting results as to its relationship with psychological factors. Objective: to determine the prevalence of signs and symptoms of this disorder and its association with emotional stress, anxiety and depression in college students of Dentistry course. Methods: therefore, we randomly selected 135 volunteers from a Brazilian public university, from a total of 344 undergratuate dental students. Exclusion criteria were: absence of two or more teeth (excluding third molars); use of a removable prosthesis; use of orthodontic appliances (fixed or mobile), at the time of the study; participants treated for orofacial pain or dysfunction; not signing the free and informed consent. The signs and symptoms of temporomandibular dysfunction were collected through a form with an appropriate history questionnaire and a clinical examination protocol. To estimate the presence of psychological factors we used the scale Hospital Anxiety and Depression, translated and validated to Portuguese. Data were tabulated and analyzed descriptively and statistically. Associations between variables, emotional stress, anxiety, depression and dysfunction were verified by statistical tests chi-square (x2) and Fisher's exact, with p< 0.05. Results: 76.3 % had dysfunction, and in 54.1 % it was considered mild, while in 22.2 % were observed active treatment needs. 34.1 % of the sample had only affected joint clinical signs. Emotional tension is statically associated with the presence of disorder and need of treatment. Anxiety and depression are associated only with the need for treatment. Conclusion: the prevalence of Temporomandibular Disorders in the sample of college students was high, with higher frequency of joint clinical signs and associated with the female gender, emotional stress, anxiety and depression.